Effect on growth attributes, yield, and economics of mustard on different levels of irrigation and microbes: Effect on growth attributes, yield, and economics of mustard on different levels of irrigation and microbes - DIKSHA TAJANE; BEENA NAIR; SANDEEP KAMADI; SWAPNIL THAKARE; SHARAD BHURE (Journal of Oilseeds Research, 2023)
The plant height, number of branches/plants, number of siliqua/plants, yield/plant, and test weight was greater in two irrigations along with seed treatment with MRD 17. A similar trend was noticed with respect to seed yield; however, it was on par with M2S2 (One Irrigation at 35 DAS along with MKS 6). seed yield/ha was observed highest in the treatment of two irrigation at 35 DAS and 65 DAS along with the microbial application of MRD 17 as a seed treatment during sowing.